2010
DOI: 10.1002/uog.7443
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic prediction of homozygous α0‐thalassemia using placental thickness, fetal cardiothoracic ratio and middle cerebral artery Doppler: alone or in combination?

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 18 publications
3
88
2
Order By: Relevance
“…A cardiothoracic ratio greater than 0.5 before 17 weeks or 0.52 after 18 weeks is considered abnormal (Figure 1). 29 , 30 …”
Section: Sonographic Markers Of Fetal α‐Thalassemia Majormentioning
confidence: 99%
“…A cardiothoracic ratio greater than 0.5 before 17 weeks or 0.52 after 18 weeks is considered abnormal (Figure 1). 29 , 30 …”
Section: Sonographic Markers Of Fetal α‐Thalassemia Majormentioning
confidence: 99%
“…Although fetal MCA-PSV is considered the best noninvasive marker in Rhesus isoimmunization, there is no enough data demonstrating that MCA-PSV is as effective in predicting alpha-thalassemia major. Leung et al [13] reported that using MCA-PSV as a parameter in prediction of alpha-thalassemia major during GA 16-20 weeks, the diagnosis may be delayed in 25% of affected pregnancies. Furthermore, by the combination of cardiothoracic ratio (CTR) and MCA-PSV, it tended to increase the sensitivity at GA 12-15 weeks (100%) and decreased the false positive rate at GA 16-20 weeks (0%).…”
Section: Ultrasound Featuresmentioning
confidence: 99%
“…Ultrasound screening is an essential part of early prenatal diagnosis for Hb Bart’s disease before development of hydropic changes. Of ultrasound markers, cardiac diameter to thoracic diameter (C/T) ratio is most accurate in predicting the fetal disease [1,2]. In our practice, C/T ratio is the most common sonomarker used for predicting fetal Hb Bart’s disease.…”
Section: Introductionmentioning
confidence: 99%